2007
DOI: 10.1515/jpm.2007.051
|View full text |Cite
|
Sign up to set email alerts
|

Gastroschisis: primary closure using umbilical cord strengthened by a polypropylene mesh

Abstract: The technique described is useful and easily applicable in children with abdominal wall defects when primary anatomic closure is not feasible. It also prevents future herniation through the anatomical defect of the abdominal wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…The umbilical patch proved to be solid, and any kind of strengthening during the procedure was not needed. Reinforcement of the defect with man-made material results in ventral hernias in 60-62% of cases after closure, and a hernia repair is required in 21% [2,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The umbilical patch proved to be solid, and any kind of strengthening during the procedure was not needed. Reinforcement of the defect with man-made material results in ventral hernias in 60-62% of cases after closure, and a hernia repair is required in 21% [2,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Gastroschisis is a congenital defect, in which the abdominal wall of newborns is not fully closed (Hernández Siverio et al, 2007). The exact causes that lead to this condition are unknown (Feldkamp et al, 2007;D'Antonio et al, 2015;Schwartz and Timmapuri, 2017).…”
Section: Fresh Huc As a Regenerative Patch To Treat Gastroschisismentioning
confidence: 99%
“…HUC Mesenchymal Stem Cells (MSCs), especially those isolated from the Wharton's Jelly (WJ), are already being used in clinical trials which have reported safety and efficacy in wound healing (Couto et al, 2019). HUC patches have been used in clinical practice with proven reparative effects for gastroschisis, and in preclinical assays for spina bifida and foot ulcers (Hernández Siverio et al, 2007;Papanna et al, 2015b;Caputo et al, 2016). However, much of the information from research and clinical uses of HUC and its byproducts is poorly defined, leading to data misinterpretation and misuse.…”
Section: Introductionmentioning
confidence: 99%
“…Одни исследователи предпочитают зашивать фасциальный дефект, другие описывают использование пуповинного остатка в каче-стве биологического протеза для укрытия дефекта брюш-ной стенки [48,49]. Синтетический протез также может быть применен для закрытия отверстия в апоневрозе [50]. Необходимо стремиться по возможности сохранить пупо-винный остаток для формирования в будущем пупка у ре-бенка [51,52].…”
Section: гастрошизисunclassified